(untitled) (African Journal of Biomedical Research, 2021)
Waste management especially medical waste is essential to preservation of health and integrity of the environment. There are several factors that may influence the adequacy of knowledge and practice regarding waste management. The main purpose of the study was to evaluate factors that influence awareness and practice of medical waste management among healthcare workers. This was a mixed-methods study carried out from October to November 2019 at four public hospitals in EThekwini metropolitan municipality of KwaZulu-Natal province, South Africa, among doctors, nurses, laboratory staff and waste-handlers. Quantitative data were analysed using statistical analysis system (SAS) software. Results showed that respondents’ professional category was strongly associated with general knowledge of healthcare waste management, and median scores showed that a higher proportion of nurses had higher scores when compared to laboratory scientists/technicians and medical doctors. Further, general knowledge scores were significantly positively correlated with the practice scores, while waste segregation was significantly, but weakly, associated with training regarding healthcare waste differentiation (p=0.025; V=0.14). Also, knowledge of recommendations in the medical waste management implementation plan was significantly, but weakly associated with waste segregation (p=0.028; V=0.14). Findings revealed a strong correlation between training, availability of waste management related workshops, and proper medical waste management amongst healthcare workers. We conclude that knowledge appeared essential to proper waste segregation and proper medical waste management practice correlates with having the requisite knowledge about waste. We recommend that education and training in waste management be provided to all healthcare workers during formal training in addition to ongoing refresher courses through regular workshops on healthcare waste management.